Competition for nectar resources does not affect bee foraging tactic constancy. (30th March 2020) - Lichtenberg, Elinor M.; Richman, Sarah K.; Irwin, Rebecca E.; Bronstein, Judith L.
Abstract : 1. Competition alters animal foraging, including promoting the use of alternative resources. It may also impact how animals feed when they are able to handle the same food with more than one tactic. Competition likely impacts both consumers and their resources through its effects on food handling, but this topic has received little attention. 2. Bees often use two tactics for extracting nectar from flowers: they can visit at the flower opening, or rob nectar from holes at the base of flowers. Exploitative competition for nectar is thought to promote nectar robbing. If so, higher competition among floral visitors should reduce constancy to a single foraging tactic as foragers will seek food using all possible tactics. To test this prediction, field observations and two experiments involving bumble bees visiting three montane Colorado plant species ( Mertensia ciliata, Linaria vulgaris, Corydalis caseana ) were used under various levels of inter‐ and intra‐specific competition for nectar. 3. In general, individual bumble bees remained constant to a single foraging tactic, independent of competition levels. However, bees that visited M. ciliata in field observations decreased their constancy and increased nectar robbing rates as visitation rates by co‐visitors increased. 4. While tactic constancy was high overall regardless of competition intensity, this study highlights some intriguing instances in which competition and tactic constancy may be linked. Further studies investigating the cognitive underpinnings of tactic constancy should provide insight on the ways in which animals use alternative foraging tactics to exploit resources. Abstract : As competition among foragers increases, foragers may try to access food in any way possible, including by 'robbing' nectar through holes at the base of flowers. Contrary to expectation, competition levels did not affect bumble bees' tendency to mix nectar robbing with legitimate visitation (at flower opening). Bees showed high tactic constancy at all competition levels. Our results highlight the need for further research on nectar robbing from the animal perspective and on food‐handling tactic constancy.